Discourse analysis in translation studies - Munday, Jeremy; Zhang, Meifang, 1979- (Benjamins current topics, 2017)
Discourse analytic approaches are central to translator training and translation analysis, but have been somewhat overlooked in recent translation studies. This volume sets out to rectify this marginalization. It considers the evolution of the use of discourse analysis in translation studies, presents current research from ten leading figures in the field and provides pointers for the future. Topics range from close textual analysis of cohesion, thematic structure and the interpersonal function to the effects of global English and the discourses of cyberspace. The inherent link between discourse and the construction of power is evident in many contributions that analyse institutional power and the linguistic resources which mark translator/interpreter positioning. An array of scenarios and languages are covered, including Arabic, Chinese, English, German, Korean and Spanish.